PERAN LITERASI KEUANGAN DALAM PENGELOLAAN KEUANGAN MAHASISWA - Adi Waluyo, Fikqi Indra; Marlina, Maria Asumpta Evi (Accounting Study Program, Universitas Ciputra Surabaya, 2019)
The purpose of this study is to explore the role of financial literacyfor students in managing their finances. This research is based on datathat shows student financial literacy in an accounting class is still low. Theresearch method used in this research is descriptive qualitative method. Thisresearch conducted in an accounting study program at a university thatbased on entrepreneurship learning. Participants in this study were studentsin the fifth semester who met the criteria in the research. Data collectionconducted by interviewing four students who met the criteria. The results ofthis study indicate that financial literacy plays a role for students in managingtheir finances. The role show in several stages. These stages are the stagesof determining the source of funds, the stage of use of funds, the stage of riskmanagement, and the future planning stage. Another finding in this studywas that the existence of technology and education became the supportingstudents in implementing financial literacy.